STUDENTS’ PERCEPTION ON THE USE OF GESCHOOL IN LEARNING ENGLISH AT SMPN 33 PADANG - Fitria Eka Putri; Martin Kustati; Luli Sari Yustina (Journal Cerdas Mahasiswa, 2022)
This paper investigates students’ perception on the use of Geschool in learning English during Covid-19 pandemic at SMPN 33 Padang. This study employed a descriptive quantitative method. A set of questionnaires has been distributed to a sample of 92 students of VIII grade SMPN 33 Padang. The findings indicated that the students have positive perceptions toward the use of Geschool in learning English. However, there were several challenges that were faced by the students such as poor connection, lack of knowledge about the internet in computers, the problem about data packages, and the last problem about less communication and interaction. In summary, overall data still shows that the respondents have a good perception on the use of Geschool in learning English during covid-19 pandemic although faced several challenges.